Early development and larval behaviour of two clingfishes, Lepadogaster purpurea and Lepadogaster lepadogaster (Pisces: Gobiesocidae) - Tojeira, Inês (2012)
The recent revision on the taxonomic status of Lepadogaster lepadogaster resulted in the division of this species into L. lepadogaster and L. purpurea, the clarification of each species’ distribution ranges and the elimination of L. zebrina (now in synonymy with L. lepadogaster). This new taxonomic status led to the need of clarifying the early development of the two species. Embryonic development lasted 21 days in L. purpurea at a mean temperature of 14.2°C, and 16 days in L. lepadogaster at a mean temperature of 16.5°C. Newly hatched larvae of both species measured 5.2 mm, had the mouth and anus opened, pigmented eyes and almost no yolk. At hatching and throughout development the two species can be distinguished by the ventral pigmentation which is absent in L. purpurea. The change to a benthic mode of life was gradual in both species, with larvae increasingly spending more time close to the bottom until definitely settling. Larval development lasted 33 days in L. purpurea at a mean temperature of 14.6°C and 18 days in L. lepadogaster at a mean temperature of 16.5°C. Locomotion and foraging behaviours are described for both species. L. lepadogaster showed a higher frequency of swimming and foraging behaviour when compared with L. purpurea.